Parvovirus B19 in an Immunocompetent Adult Patient with Acute Liver Failure: An Underdiagnosed Cause of Acute Non-A-E Viral Hepatitis - J Kee Ho; Susan PL Tha; Robert Coupland; Bakul I Dalal; William R Bowie; Gayatri M Sreenivasan; Mel Krajden; Eric M Yoshida (Canadian Journal of Gastroenterology)
There are occasional pediatric reports of parvovirus B19-associated transient acute hepatitis and hepatic failure. A case of a 34-year-old immunocompetent woman who developed severe and prolonged but self-limited acute hepatitis and myelosuppression following acute parvovirus B19 infection is reported. Parvovirus B19 may be the causative agent in some adult cases of acute non-A-E viral hepatitis and acute liver failure.